Our hands are tied! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A representative from Cameroon?s Ministry of Agriculture describes how liberalisation has affected farmers, and what the government is doing to support them. Rules imposed by the International Monetary Fund have limited what the government can do.